Wildlife species diversity in oli complex of Kainji Lake National Park, Nigeria (2022)
The survey of wildlife species diversity is important for management and decision making in Wildlife rks in order to achieve effective conservation. Up-to-date information on the diverse fauna species in Kainji Lake National Park is scarce. Therefore, wild animal species diversity in the National Park was assessed. The line transect and total enumeration count methods were used in the study. Oli Complex was stratified into five line transects laid at 5 km intervals and then a census of wild animals was taken following standard procedures. Data were analysed using descriptive and inferential statistics. Fiftynine taxa were identified with 4,665 individuals enumerated. A total of 24 Mammalia, 24 Avifauna, 8 Reptilia, 1 Amphibia, and 2 Mollusca species were identified. Buffon's kob (Kobus kob kob) was the most abundant (2,019), followed by the Olive baboon (Papio anubis) (963), helmeted Guinea fowl (Numidea melagris) (189), and Red Flanked (RF) duiker (Cephalophus rufilatus) (118). Dominance was low (0.2) with high diversity index (0.8), and low evenness (0.2); that was moderately spread but not equally (0.6) distributed within the study area. Buffon's kob had the highest relative importance index (24.13%), while Guinea fowl had the least (3.27%). Buffon's kob had the highest density (40.38/ km2), followed by Olive baboon (19.26/km2), Guinea fowl (3.78/km2), Roan antelope (3.32/ km2), and Red Flanked duiker (2.36/ km2). Oli Complex of Kainji Lake National Park had a high wildlife diversity and supported a wide range of animal species.